Evaluating the impact of three progestin-based hormonal contraceptive methods on immunologic changes in the female genital tract and systemically (CHIME Study): a prospective cohort study protocol - Lisa B. Haddad; Gina Bailey Herring; C. Christina Mehta; Tyree Staple; Marisa R. Young; Sakthivel Govindaraj; Vijayakumar Velu; Alicia K. Smith (BMC, 2022)
Abstract Background Gonadal hormones can modify immune function, which may impact susceptibility to infectious diseases, including Human Immunodeficiency Virus (HIV). There is limited knowledge about how hormonal contraceptives (HC) influence the immune response during the course of use. The CHIME study aims to evaluate the effect of long-acting progestin-based hormonal contraceptives (depot medroxyprogesterone acetate, etonogestrel implant, and levonorgestrel intrauterine device) on immunologic changes in the female genital tract (FGT) and systemic compartment. Methods CHIME is an observational cohort study where participants attend 2 visits prior to initiating the HC method of their choice, and then attend 6 visits over 12 months with biological sampling (vaginal swabs, cervicovaginal lavage, cytobrush and blood) for immunological, bacteriological, and virological analyses at each visit. Immune profiling will be evaluated by multi-color flow cytometry to determine how different T-cell subsets, in particular the CD4 T-cell subsets, change during the course of contraceptive use and whether they have different profiles in the FGT compared to the systemic compartment. The study aims are (1) to characterize the alterations in FGT and systemic immune profiles associated with three long-acting progestin-only HC and (2) to evaluate the vaginal microenvironment, determined by 16 s rRNA sequencing, as an individual-level risk factor and moderator of genital and systemic immune profile changes following exposure to three commonly used HC. Data collection started in March 2019 and is scheduled to be completed in October 2024. Discussion The CHIME study aims to contribute to the body of research designed to evaluate the comparative impact of three long-acting progestin-only HC on innate and adaptive immune functions to understand how immunologic effects alter STI and HIV susceptibility.